Religious Diversity in European Prisons: Challenges and Implications for Rehabilitation - Becci, Irene (Springer, 2015)
This book examines how prisons meet challenges of religious diversity, in an era of increasing multiculturalism and globalization. Social scientists studying corrections have noted the important role that religious or spiritual practice can have on rehabilitation, particularly for inmates with coping with stress, mental health and substance abuse issues. In the past, the historical figure of the prison chaplain operated primarily in a Christian context, following primarily a Christian model. Increasingly, prison populations (inmates as well as employees) display diversity in their ethnic, cultural, religious and geographic backgrounds. As public institutions, prisons are compelled to uphold the human rights of their inmates, including religious freedom. Prisons face challenges in approaching religious plurality and secularism, and maintaining prisoners' legal rights to religious freedom.